ChemInform Abstract: Exploiting the σ‐Phylic Properties of Cationic Gold(I) Catalysts in the Ring Opening Reactions of Aziridines with Indoles. Issue 45 (October 2016) - Rossi, Elisabetta; Abbiati, Giorgio; Dell'Acqua, Monica; Negrato, Marco; Paganoni, Andrea; Pirovano, Valentina
Abstract: Starting from 2‐substituted indoles the title transformation gives rise to a large range of tryptamine derivatives.